Internationalization of Arts Universities : Towards Social Sustainability - Niemensivu, Outi (Taideyliopiston Sibelius-Akatemia, 2024)
This doctoral dissertation on the internationalization of arts universities draws on the idea that arts and culture can be used as a mediator in advancing social sustainability. The aim is to understand how and to what extent the internationalization of arts universities contributes to social sustainability in the domestic context as perceived by stakeholders within the university: senior managers, faculty, and students. The focus is on how higher music education institutions within arts universities advance social sustainability in forms such as diversity, inclusion, equity, social well-being, and social cohesion by engaging with difference. As a part of its third mission, an arts university can contribute to the cohesion and interaction between culturally diverse members of society. This interdisciplinary arts management research draws on three theoretical discussions: the internationalization of higher education, sustainability, and community engagement. Within sustainability the focus is on social sustainability. The research is a qualitative case study of two European arts universities and their higher music education institutions: University of the Arts Helsinki and University of Music and Performing Arts Graz. This study proposes that to be socially sustainable in the domestic intercultural context, traditional music education should be reimagined in cooperation with all levels of music education. Lowering the barriers raised by the elitism of music education, the dominance of Western classical music, and a narrowly defined view of quality requires a change in the strategy, governance, and policies of the institutions. Proactive engagement with local communities, the participation of the whole university community as well as collaboration with local communities and external partners are requisites for a shift towards social sustainability. This research contributes to the scholarly discourse on the social and societal impact of arts universities. It extends the research of the internationalization of higher education into arts universities and their higher music education institutions with an interdisciplinary approach. The research offers fresh perspectives and emerging visions for stakeholders related to international activities within and outside arts and scientific universities as well as for internationalization scholars.

Tämän taideyliopistojen kansainvälistymistä käsittelevän tutkimuksen tavoitteena on ymmärtää, miten ja missä määrin taideyliopistojen kansainvälistyminen ja sosiaalinen kestävyys kohtaavat toisensa paikallisessa kulttuurien välisessä kontekstissa. Tutkimus keskittyy siihen, miten taideyliopistojen musiikkikorkeakoulut edistävät taiteen ja kulttuurin avulla sosiaalista kestävyyttä, kuten esimerkiksi moninaisuutta, inkluusiota, oikeudenmukaisuutta sekä sosiaalista hyvinvointia ja yhteenkuuluvuutta erilaisuuden kohtaamisen kautta. Taideyliopisto voi osana kolmatta, yhteiskunnallista tehtäväänsä vaikuttaa positiivisesti erilaisista kulttuureista tulevien ihmisten vuorovaikutukseen ja yhteenkuuluvuuteen. Taidejohtamisen alaan liittyvä poikkitieteellinen tutkimus asemoituu kolmeen tieteelliseen keskusteluun: yliopistojen kansainvälistyminen, kestävyys ja yhteisöjen osallistaminen (community engagement). Kestävyydessä tutkimus keskittyy sosiaaliseen kestävyyteen. Laadullisessa tapaustutkimuksessa tutkitaan kahta eurooppalaista taideyliopistoa ja niiden musiikkikorkeakoulua: Helsingin Taideyliopistoa sekä Grazin Musiikin ja esittävän taiteen yliopistoa. Jotta perinteinen musiikin koulutus olisi sosiaalisesti kestävää, sitä on tarkasteltava uudesta näkökulmasta yhteistyössä alan kaikkien toimijoiden kanssa. Musiikkikoulutuksen elitismin, läntisen klassisen musiikin valta-aseman ja kapeasti määritellyn laatukäsityksen luomien esteiden madaltaminen edellyttää muutoksia instituutioiden strategiassa, johtamisessa ja toimintatavoissa. Proaktiivinen ja vastavuoroinen toiminta paikallisten yhteisöjen kanssa, koko yliopistoyhteisön osallistuminen sekä yhteistyö paikallisten yhteisöjen ja yhteistyökumppanien kanssa ovat edellytyksiä muutoksessa kohti sosiaalista kestävyyttä. Tutkimus kontribuoi yliopistojen sosiaalisen ja yhteiskunnallisen vaikuttavuuden tieteelliseen keskusteluun. Se myös laajentaa yliopistojen kansainvälistymisen tutkimusalan taideyliopistoihin ja niiden musiikkikorkeakouluihin poikkitieteellisellä lähestymistavalla. Tutkimus tarjoaa uusia näkökulmia ja orastavia visioita taide- ja tiedeyliopistojen kansainvälistymisen parissa työskenteleville tahoille.
Keywords: yhteisöjen osallistaminen; taideyliopisto; taidejohtaminen; taidekorkeakoulut; kansainvälistyminen; musiikki; korkeakouluopetus; yliopistot; sosiaalinen kestävyys; kulttuurinen kestävyys; MuTri